2009
DOI: 10.1177/0146167208331337
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unfair Treatment on Depressive Mood: The Moderating Role of Self-Esteem Level and Self-Esteem Instability

Abstract: This research examines the moderating roles of self-esteem level and self-esteem instability in the relationship between perceived unfair treatment and depressive mood. Based on the assumption that unfairness is a threat to one's social standing and self-esteem, the authors proposed that individuals with highly fragile self-esteem (i.e., the combination of unstable and high self-esteem) react more strongly when experiencing unfair treatment. This hypothesis was tested in a real-world setting using cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 69 publications
0
26
2
Order By: Relevance
“…This finding contradicts the result of a previous study, which found that people high in narcissism report higher interpersonal transgression (e.g., failure to be appreciated adequately) than people low on narcissism (McCullough, Emmons, Kilpatrick, & Mooney, 2003). However, a pattern similar to the one found in the current paper was reported in a study on the effect of perceived unfairness of supervisors' behaviour among employees with high but unstable self-esteem (Meier, Semmer, & Hupfeld, 2009). Similarly to narcissists, people with high but unstable self-esteem have positive self-feelings that are fragile and need continual validation (cf.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contradicts the result of a previous study, which found that people high in narcissism report higher interpersonal transgression (e.g., failure to be appreciated adequately) than people low on narcissism (McCullough, Emmons, Kilpatrick, & Mooney, 2003). However, a pattern similar to the one found in the current paper was reported in a study on the effect of perceived unfairness of supervisors' behaviour among employees with high but unstable self-esteem (Meier, Semmer, & Hupfeld, 2009). Similarly to narcissists, people with high but unstable self-esteem have positive self-feelings that are fragile and need continual validation (cf.…”
Section: Discussioncontrasting
confidence: 99%
“…Employees with high but unstable self-esteem did not perceive their supervisor's behaviour to be more unfair than employees with a high and stable self-esteem. However, they reacted most strongly to unfair treatment (Meier et al, 2009). Thus, the effect of narcissism or a high but unstable self-esteem seems to lie in a higher vulnerability to an imbalance or unfairness, rather than in a general feeling of not being treated adequately.…”
Section: Discussionmentioning
confidence: 90%
“…As previously mentioned, research has supported a link between interpersonal workplace interactions and subsequent affective states (e.g., Bono, Foldes, Vinson, & Muros, 2007; Meier et al, 2009; Tschan, Rochat, & Zapf, 2005; Vittengl & Holt, 1998; Xanthopoulou et al, 2009). In terms of the main effects of workplace interactions on affective states, self‐determination theory (Ryan & Deci, 2000) provides one possible explanation for this link.…”
Section: Interpersonal Interactions and Affective Statesmentioning
confidence: 91%
“…For example, Xanthopoulou, Bakker, Demerouti, and Schaufeli (2009) reported that supervisory coaching added to an employee's reserve of job resources and increased employee engagement and performance. In addition, Meier, Semmer, and Hupfeld (2009) found that the experience of unfair treatment by one's supervisor was related to subsequent depressive mood for individuals with an unstable high self‐esteem. Overall, research has begun to show that interpersonal interactions are an important part of employees' daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…While there is debate in the literature on the causal direction of the discrimination-self-esteem association [44], it may be that some groups of individuals who experience interpersonal discrimination internalize some of the negative social devaluation of their group leading to lowered self-esteem [45] (and other poor mental health outcomes [46-49]), suggesting a mediating role. On the other hand, other study findings suggest that, similar to optimism, higher self-esteem is associated with lower likelihoods of perceiving interpersonal discrimination [50] suggesting a confounding role.…”
Section: Introductionmentioning
confidence: 99%